2020
DOI: 10.1016/j.vaccine.2019.10.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal antibodies on the cellular immune response after infant vaccination: A review

Abstract: During the last few decades, maternal immunization as a strategy to protect young infants from infectious diseases has been increasingly recommended, yet some issues have emerged. Studies have shown that for several vaccines, such as live attenuated, toxoid and conjugated vaccines, high maternal antibody titers inhibit the infant's humoral immune response after infant vaccination. However, it is not clear whether this decreased antibody titer has any clinical impact on the infant's protection, as the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
2
22
0
2
Order By: Relevance
“…This notion is consistent with our current understanding of the programming of the immune system in early life, which adapts to meet environmental demands during fetal life and after birth [2]. Interestingly, maternal antibodies can reduce the magnitude of antibody responses to routine vaccines in infants but do not appear to impact T cell responses [4,15]. The impact of maternal antibodies on the quality of infant B and T cell responses and the mechanisms involved remain largely unknown.…”
Section: Interactions Of Maternal Antibodies With the Infant Immune Ssupporting
confidence: 79%
“…This notion is consistent with our current understanding of the programming of the immune system in early life, which adapts to meet environmental demands during fetal life and after birth [2]. Interestingly, maternal antibodies can reduce the magnitude of antibody responses to routine vaccines in infants but do not appear to impact T cell responses [4,15]. The impact of maternal antibodies on the quality of infant B and T cell responses and the mechanisms involved remain largely unknown.…”
Section: Interactions Of Maternal Antibodies With the Infant Immune Ssupporting
confidence: 79%
“…Whether these results apply to human infants and other antigens needs to be determined. Finally, while B cell responses are inhibited in the presence of maternal antibodies, scarce data support that T cell responses are detected in the presence of maternal antibodies (191).…”
Section: Mechanism Of Interferencementioning
confidence: 90%
“…A lowered antibody titre, caused by the blunting effect, does not necessarily imply reduced protection; a recent comprehensive review concluded that in the majority of both human and animal studies, priming of CMI after infant vaccination occurred even in the presence of high maternal antibody titres, with minimal or no blunting effect on cellular responses reported (Orije et al, 2020). Furthermore, in two studies, maternal antibodies were even found to stimulate a more robust CMI response, highlighting a potential secondary beneficial effect of maternal immunization (Bertley et al, 2004;Rowe et al, 2005).…”
Section: Systemic Infant Cellular Immunitymentioning
confidence: 99%